Effects of gut microbiota on neurodegenerative diseases - Khatoon, Saima; Kalam, Nida; Rashid, Summya; Bano, Gulnaz (Frontiers in Aging Neuroscience, 2023)
A progressive degradation of the brain’s structure and function, which results in a reduction in cognitive and motor skills, characterizes neurodegenerative diseases (NDs) such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD). The morbidity linked to NDs is growing, which poses a severe threat to human being’s mental and physical ability to live well. The gut-brain axis (GBA) is now known to have a crucial role in the emergence of NDs. The gut microbiota is a conduit for the GBA, a two-way communication system between the gut and the brain. The myriad microorganisms that make up the gut microbiota can affect brain physiology by transmitting numerous microbial chemicals from the gut to the brain via the GBA or neurological system. The synthesis of neurotransmitters, the immunological response, and the metabolism of lipids and glucose have all been demonstrated to be impacted by alterations in the gut microbiota, such as an imbalance of helpful and harmful bacteria. In order to develop innovative interventions and clinical therapies for NDs, it is crucial to comprehend the participation of the gut microbiota in these conditions. In addition to using antibiotics and other drugs to target particular bacterial species that may be a factor in NDs, this also includes using probiotics and other fecal microbiota transplantation to maintain a healthy gut microbiota. In conclusion, the examination of the GBA can aid in understanding the etiology and development of NDs, which may benefit the improvement of clinical treatments for these disorders and ND interventions. This review indicates existing knowledge about the involvement of microbiota present in the gut in NDs and potential treatment options.